Systems Engineering roles to handle emergent properties and behaviors in complex technical systems - Gräßler, Iris; Pfeifer, Jan Niklas; Hintz, Florian; Meyrl, Nicolas (INCOSE International Symposium)
Abstract Engineering projects for complex technical systems such as automobiles demand extensive requirement specifications and corresponding hierarchy levels in system architectures. Especially when considering emergent phenomena, such as total weight or aerodynamics, a closely networked collaboration of discipline‐specific and cross‐disciplinary roles is required. Further, in large organizations with a group structure, resulting functional and non‐functional contents need to be managed by distinct Systems Engineering roles. For example, the role “property manager” takes care of achieving overarching product properties, such as weight or aerodynamics, which cannot be directly fixed, but result from many specifications. This paper proposes new Systems Engineering roles and their application in a German Original Equipment Manufacturer (OEM). For validation, the roles have already been applied in everyday engineering projects at the OEM. The concept proved to be indispensable and transferable to other Systems Engineering projects.
Keywords: Systems Engineering roles; properties; features; emergent phenomena; automotive

The new TISTRAQ process: Solution treatment with rapid quenching and annealing for Ti-6Al-4V sheet metal part forming - the effect of processing parameters on microstructure and mechanical properties - Pfeffer, Nina; Kaiser, Maximilian Alexander; Meyer, Thomas; Göken, Mathias; Höppel, Heinz Werner (IOM3. Chapter 14: Forming, Machining & Joining [version 1; not peer reviewed])
The phase and TTT diagrams of the Ti-6Al-4V system allow the development of a new forming process for a more energy- and materialefficient production of sheet metal parts. This new “TISTRAQ” process is composed of two steps. In terms of process technology, the first step is comparable to a direct press-hardening process already well known for steels. In this step, the Ti-6Al-4V sheet material is resistively heated to a temperature below β-transus Tβ and, after a very short holding time, simultaneously formed and quenched by use of water cooled tools. Thereby, the β phase undergoes a martensitic transformation. The second step is a subsequent short-time annealing, which leads to a hardening of the material. In this work, a new test rig using resistive heating technique was used in order to produce different solution treated and tool quenched (STQ) and subsequently annealed (STA) states. In this paper, the effects of heating rate, solution treatment temperature and holding time on microstructure and mechanical properties are addressed. For the characterisation, tensile testing and scanning electron microscopy were used. By the systematic variation of applied processing parameters, dominating effects on microstructure and mechanical properties were evaluated. For example, the solution treatment temperature was found to have a significant effect on microstructural features and characteristic strength and strain values. The obtained results reveal a high potential for future technical applications.
Keywords: Ti-6Al-4V; thermomechanical processing; resistive heating; quench-forming; process parameter-microstructure-properties relationship

Guaranteeing Properties of Reconfigurable Hardware Circuits with Proof-Carrying Hardware - Wiersema, Tobias
Previous research in proof-carrying hardware has established the feasibility and utility of the approach, and provided a concrete solution for employing it for the certification of functional equivalence checking against a specification, but fell short in connecting it to state-of-the-art formal verification insights, methods and tools. Due to the immense complexity of modern circuits, and verification challenges such as the state explosion problem for sequential circuits, this restriction of readily-available verification solutions severely limited the applicability of the approach in wider contexts. This thesis closes the gap between the PCH approach and current advances in formal hardware verification, provides methods and tools to express and certify a wide range of circuit properties, both functional and non-functional, and presents for the first time prototypes in which circuits that are implemented on actual reconfigurable hardware are verified with PCH methods. Using these results, designers can now apply PCH to establish trust in more complex circuits, by using more diverse properties which they can express using modern, efficient property specification techniques.
Keywords: Proof-Carrying Hardware; Formal Verification; Sequential Circuits; Non-Functional Properties; Functional Properties

A DC bias approach to the characterisation of non-linear material parameters of piezoelectric ceramics - Dreiling, Dmitrij; Feldmann, Nadine; Henning, Bernd
Keywords: piezoelectric materials; piezoelectric properties; DC bias field; non-linear material parameters

Synthesis of lead-free piezoelectric powders by ultrasonic-assisted hydrothermal method and properties of sintered (K0.48Na0.52)NBO3 ceramics - Isobe, G.; Maeda, Takafumi; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Ultrasonics, Ferroelectrics, and Frequency Control, IEEE Transactions on)
(K,Na)NbO3 ceramics have attracted much attention as lead-free piezoelectric materials with high piezoelectric properties. High-quality (K,Na)NbO3 ceramics can be sintered using KNbO3 and NaNbO3 powders synthesized by a hydrothermal method. In this study, to enhance the quality factor of the ceramics, high-power ultrasonic irradiation was employed during the hydrothermal method, which led to a reduction in the particle size of the resultant powders.
Keywords: Q-factor; ceramics; crystal growth from solution; particle size; piezoelectric materials; potassium compounds; powders; sintering; sodium compounds; ultrasonic effects; (K0.48Na0.52)NbO3; KNbO3 powders; NaNbO3 powders; high-power ultrasonic irradiation; lead-free piezoelectric materials; lead-free piezoelectric powders; particle size reduction; piezoelectric properties; quality factor; sintered (K0.48Na0.52)NbO3 ceramics; sintering; ultrasonic-assisted hydrothermal method; Acoustics; Ceramics; Lead; Piezoelectric materials; Powders; Radiation effects; Transducers

Towards self-adaptive caches: A run-time reconfigurable multi-core infrastructure - Ho, Nam; Kaufmann, Paul; Platzner, Marco (2014 IEEE Intl. Conf. on Evolvable Systems (ICES))
Keywords: Linux; cache storage; embedded systems; granular computing; multiprocessing systems; reconfigurable architectures; Leon3 SPARe processor; custom logic events; evolvable-self-adaptable processor cache; fine granular profiling; integer unit events; measurement infrastructure; microarchitectural events; multicore embedded system; perf_event standard Linux performance measurement interface; processor properties; run-time reconfigurable memory-to-cache address mapping engine; run-time reconfigurable multicore infrastructure; split-level caching; Field programmable gate arrays; Frequency locked loops; Irrigation; Phasor measurement units; Registers; Weaving

Parameter estimation and classification of censored Gaussian data with application to WiFi indoor positioning - Hoang, Manh Kha; Haeb-Umbach, Reinhold (38th International Conference on Acoustics, Speech, and Signal Processing (ICASSP 2013))
In this paper, we consider the Maximum Likelihood (ML) estimation of the parameters of a GAUSSIAN in the presence of censored, i.e., clipped data. We show that the resulting Expectation Maximization (EM) algorithm delivers virtually biasfree and efficient estimates, and we discuss its convergence properties. We also discuss optimal classification in the presence of censored data. Censored data are frequently encountered in wireless LAN positioning systems based on the fingerprinting method employing signal strength measurements, due to the limited sensitivity of the portable devices. Experiments both on simulated and real-world data demonstrate the effectiveness of the proposed algorithms.
Keywords: Gaussian processes; Global Positioning System; convergence; expectation-maximisation algorithm; fingerprint identification; indoor radio; signal classification; wireless LAN; EM algorithm; ML estimation; WiFi indoor positioning; censored Gaussian data classification; clipped data; convergence properties; expectation maximization algorithm; fingerprinting method; maximum likelihood estimation; optimal classification; parameters estimation; portable devices sensitivity; signal strength measurements; wireless LAN positioning systems; Convergence; IEEE 802.11 Standards; Maximum likelihood estimation; Parameter estimation; Position measurement; Training; Indoor positioning; censored data; expectation maximization; signal strength; wireless LAN

Vibrational Fingerprints of LiNbO3-LiTaO3Mixed Crystals - Sanna, Simone; Riefer, A.; Neufeld, Sergej; Schmidt, Wolf Gero; Berth, Gerhard; Rüsing, Michael; Widhalm, A.; Zrenner, Artur (Ferroelectrics)
Atomistic simulations in the framework of the density functional theory have been used to model morphologic and vibrational properties of lithium niobate–lithium tantalate mixed crystals as a function of the [Nb]/[Ta] ratio. Structural parameters such as the crystal volume and the lattice parameters a and c vary roughly linearly from LiTaO3 to LiNbO3, showing only minor deviations from the Vegard behavior. Our ab initio calculations demonstrate that the TO1, TO2 and TO4 vibrational modes become harder with increasing Nb concentration. TO3 becomes softer with increasing Nb content, instead. Furthermore, the investigated zone center A1 -TO phonon modes are characterized by a pronounced stoichiometry dependence. Frequency shifts as large as 30 cm−1 are expected as the [Nb]/[Ta] ratio grows from 0 to 1. Therefore, spectroscopic techniques sensitive to the A1 modes (such as Raman spectroscopy), can be employed for a direct and non-destructive determination of the crystal composition.
Keywords: Ferroelectrics; vibrational properties; LiNbO3; LiTaO3; mixed crystals

Non-perturbing cavitation detection / monitoring in sonochemical reactors - Bornmann, Peter; Hemsel, Tobias; Sextro, Walter; Maeda, Takafumi; Morita, Takeshi (Ultrasonics Symposium (IUS), 2012 IEEE International)
To optimize the ultrasound irradiation for cavitation based ultrasound applications like sonochemistry or ultrasound cleaning, the correlation between cavitation intensity and the resulting effect on the process is of interest. Furthermore, changing conditions like temperature and pressure result in varying acoustic properties of the liquid. That might necessitate an adaption of the ultrasound irradiation. To detect such changes during operation, process monitoring is desired. Labor intensive processes, that might be carried out for several hours, also require process monitoring to increase their reliability by detection of changes or malfunctions during operation. In some applications cavitation detection and monitoring can be achieved by the application of sensors in the sound field. Though the application of sensors is possible, this necessitates modifications on the system and the sensor might disturb the sound field. In other applications harsh, process conditions prohibit the application of sensors in the sound field. Therefore alternative techniques for cavitation detection and monitoring are desired. The applicability of an external microphone and a self-sensing ultrasound transducer for cavitation detection were experimentally investigated. Both methods were found to be suitable and easily applicable.
Keywords: cavitation; chemical reactors; microphones; process monitoring; reliability; ultrasonic applications; ultrasonic waves; acoustic properties; cavitation based ultrasound applications; cavitation intensity; change detection reliability; external microphone; malfunction detection reliability; nonperturbing cavitation detection; nonperturbing cavitation monitoring; process monitoring; self-sensing ultrasound transducer; sonochemical reactors; sonochemistry; ultrasound cleaning; ultrasound irradiation; Acoustics; Liquids; Monitoring; Sensors; Sonar equipment; Transducers; Ultrasonic imaging

Vibrational fingerprints of LiNbO3-LiTaO3 mixed crystals - Sanna, Simone; Riefer, Arthur; Neufeld, Sergej; Schmidt, Wolf Gero; Berth, Gerhard; Widhalm, Alex; Zrenner, Artur (Proceedings of ISAF-ECAPD-PFM 2012)
The structural and vibrational properties of lithium niobate (LN) – lithium tantalate (LT) mixed crystals (LNT, LiNb1-xTaxO3) are investigated over the whole composition range by first-principles simulations. The crystal volume grows roughly linearly from LT to LN, whereby the lattice parameters a and c show minor deviations from the Vegard behavior between the end compounds, LiNbO3 and LiTaO3. Our calculations in the framework of the density functional theory show the TO1, TO2 and TO4-modes to become harder with increasing Nb concentration. TO3 becomes softer with increasing Nb content, instead. The frequency shifts of the zone center A1-TO phonon modes for crystals with different compositions are found to be as large as 30 cm-1. Raman spectroscopy, which is sensitive to the A1 modes, can be therefore employed to determine the crystal composition.
Keywords: Ferroelectrics; Vibrational properties; LiNbO3; LiTaO3; Mixed Crystals

Blogs as Objects of Preservation: Advancing the Discussion on Significant Properties - Stepanyan, Karen; Gkotsis, George; Kalb, Hendrik; Kim, Yunhyong; Cristea, Alexandra I.; Joy, Mike; Trier, Matthias; Ross, Seamus (iPress 2012)
challenge for the digital preservation community. While the methodological frameworks for selecting these properties provide a good foundation, a continued discussion is necessary for further clarifying and improving the available methods. This paper advances earlier work by building on the existing InSPECT framework and improving its capabilities of working with complex/compound objects like blogs. The modifications enable a more thorough analysis of object structures, accentuate the differences and similarities between the framework’s two streams of analysis (i.e. Object and Stakeholder analysis) and, subsequently, improve the final reformulation of the properties. To demonstrate the applicability of the modified framework, thepaper presents a use case of a blog preservation initiative that is informed by stakeholder interviews and evaluation of structural and technological foundations of blogs. It concludes by discussing the limitations of the approach and suggesting directions for future research.
Keywords: Blogs; Weblogs; Digital Preservation; Significant Properties

(K,Na)NbO3 lead-free piezoelectric ceramics synthesized from hydrothermal powders - Maeda, Takafumi; Takiguchi, Norihito; Morita, Takeshi; Ishikawa, Mutsuo; Hemsel, Tobias (Materials Letters)
Among various lead-free piezoelectric materials, (K,Na)NbO$_{3}$ is a very promising candidate. In this study, (K,Na)NbO$_{3}$ ceramics were sintered from mixed (K,Na)NbO$_{3}$ and NaNbO$_{3}$ powders prepared by hydrothermal reaction. These two powders were mixed with distilled water in a KNbO$_{3}$/NaNbO$_{3}$ molar ratio of 1. After sintering the mixed powder, the solid solution of (Na,K)NbO$_{3}$ ceramics was obtained. The electrical properties such as the electromechanical coupling factors k$_{p}$ and k$_{33}$, the mechanical quality factor, Q$_{m}$, and the piezoelectric constant d$_{33}$ of the sintered (K,Na)NbO$_{3}$ ceramics were 0.32, 0.48, 71 (radial mode), 118 ((33)mode), and 107 pC/N, respectively.
Keywords: Lead-free piezoelectric material; (K; Na)NbO$_{3}$ ceramics; Sintering solid solution; Piezoelectric properties

Velocity Estimation of Mobile Terminals by Exploiting GSM Downlink Signalling - Peschke, Sven; Haeb-Umbach, Reinhold (4th Workshop on Positioning Navigation and Communication (WPNC 2007))
In this paper, we experimentally evaluate algorithms for velocity estimation of a GSM 900 mobile terminal which are based on the analysis of the statistical properties of the fast fading process. It is shown how theses statistics can be obtained from the training sequences present in downlink transmission bursts without establishing an active connection. Realistic simulations of a GSM channel according to the COST 207 channel models have been conducted. These models incorporate effects like multipath propagation, fading, cochannel interference and additive noise. It is shown that velocity estimation by searching for the maximum slope of the power density spectrum of the fast fading performs best.
Keywords: additive noise; cellular radio; channel estimation; cochannel interference; COST 207 channel models; downlink transmission bursts; fading channels; fading process; GSM downlink signalling; mobile terminals; multipath channels; multipath propagation; power density spectrum; statistical analysis; statistical properties; telecommunication links; telecommunication terminals; velocity estimation

Model based design of piezoelectric generators utilizing geometrical and material properties - Richter, Björn; Twiefel, Jens; Hemsel, Tobias; Wallaschek, Jörg (ASME 2006 International Mechanical Engineering Congress and Exposition)
This paper presents a general model based on the electromechanical circuit theory. The model is set up as a mechanical equivalent model for base excited systems and describes the behaviour of a piezoelectric element around one resonance frequency which is sufficient for most practical applications. The model is extended to obtain the influence of geometrical and material properties. The derivated properties are used to describe the parameters of the general model which is easy to handle. Using this model either the calculation of the output power on a specific electric load or the determination of the design of the used piezoelectric element for a needed electric output power is possible. The paper focuses on the design of the ratio of length and width of a piezoelectric bimorph. The validity of the model is shown by the comparison of computed and experimental results.
Keywords: Materials properties; Design; Generators